CYBERBULLYING DI MEDIA SOSIAL INSTAGRAM DITINJAU DARI PERSPEKTIF ISLAM - Annastasya Sukma Setiahawa; Nirwan Syafrin; Suyud Arif (KOLONI, 2022)
This study discusses cyberbullying on social media that focuses on Instagram social media. The purpose of this study is to find out the phenomenon of cyberbullying on social media instagram ̧and to know the islamic views of cyberbullying. This study has limited problems in collecting data, namely only data in the form of comments on each post, and these posts in the period from January to June 2022. This research uses a descriptive method with a qualitative approach. In this study will describe an object and social phenomenon explained through narrative writing, the researcher will make direct observations in seeing events and also what are important things at the time of research. This qualitative research will be used to understand and analyze cyberbullying actions through comments on Instagram social media. The results of this study explain that the phenomenon of cyberbullying on social media is found in various applications, such as chat applications ̧bermain games, and through other social media based on the internet. Cyberbullying cases have increased which are divided into several categories, namely age, gender, and sexual orientation categories. In addition, in this study, data and examples of cyberbullying cases were found. This research also explains the Islamic view in looking at cyberbullying as evidenced through the surah Al-Hujuurat, Al-Humazah, and one of the hadiths contained in the book of sunan Ibnu Majah. Keywords: Social media, cyberbullying, Instagram